Предмет: Алгебра, автор: elizabet1111111111

пожааааалуйста! срочно нужно. 27 б

Приложения:

Ответы

Автор ответа: Alexandr130398
0
b) (25^{1+ sqrt{2} } -5^{2 sqrt{2} })*5^{-1-2 sqrt{2} }=(5^{2+2 sqrt{2} } -5^{2 sqrt{2} })*5^{-1-2 sqrt{2} }= \ 5^{2+2 sqrt{2} } *5^{-1-2 sqrt{2}}-5^{2 sqrt{2} }*5^{-1-2 sqrt{2}}=5^{2+2 sqrt{2} -1-2 sqrt{2} }-5^{2 sqrt{2} -1-2 sqrt{2} }\ =5-5^{-1}=5- frac{1}{5}= frac{25-1}{5} = frac{24}{5} =4.8 \  \  \

g) (2^{2 sqrt{3} }-4^{ sqrt{3} -1})*2^{-2 sqrt{3} }=2^{2 sqrt{3}}*2^{-2 sqrt{3}}-2^{2 sqrt{3} -2}*2^{-2 sqrt{3}}= \  \ =2^{2 sqrt{3}-2 sqrt{3} }-2^{2 sqrt{3} -2-2 sqrt{3} }=2 ^{0} -2^{-2}=1- frac{1}{4} = frac{3}{4} =0.75

3)  |x-3| textless  2 \ -2 textless  x-3 textless  2 \ -2+3 textless  x textless  2+3 \ 1 textless  x textless  5 \ xin (1;5) \  \ 4)b^{ sqrt{3} } (frac{1}{b}) ^{ sqrt{3} -1}=b^{ sqrt{3} }*b^{1- sqrt{3} }=b^{ sqrt{3} +1- sqrt{3} }=b
Автор ответа: elizabet1111111111
0
спасибо огромное)
Похожие вопросы
Предмет: Математика, автор: Аноним